2018
DOI: 10.1155/2018/9409868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grain Orientation on Stress State near Grain Boundary of Austenitic Stainless Steel Bicrystals

Abstract: e stress state at the crack tip of structural components in nuclear power plants used in the SCC quantitative prediction models is based on the assumption that the polycrystalline material is isotropic and homogeneous at present. However, the crystals in polycrystalline materials are anisotropic with different orientations, which would induce a nonuniform stress to cause the initiation and propagation of SCC. By using a finite element method, the elastic responses of anisotropic behaviors of austenitic stainle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[100] Considering the relationship between the [100], [110], and [111] orientations and the stretching axis, three types of crystals with different orientations were modeled [28], as shown in Table 1 As shown in Figure 3, to ensure the material coordinate o-x y z coincide with the global coordinate o-xyz, the material coordinate o-x y z should be rotated. The rotation matrices of material coordinate o-x y z with respect to the global coordinate o-xyz are [37],…”
Section: Grain Type X' Y' Z' Most Compliant (Mc)mentioning
confidence: 99%
See 1 more Smart Citation
“…[100] Considering the relationship between the [100], [110], and [111] orientations and the stretching axis, three types of crystals with different orientations were modeled [28], as shown in Table 1 As shown in Figure 3, to ensure the material coordinate o-x y z coincide with the global coordinate o-xyz, the material coordinate o-x y z should be rotated. The rotation matrices of material coordinate o-x y z with respect to the global coordinate o-xyz are [37],…”
Section: Grain Type X' Y' Z' Most Compliant (Mc)mentioning
confidence: 99%
“…Due to elastic anisotropy, the anisotropic elastic behavior of microstructure at grain boundaries can produce local stress concentrations [27] and strong hydrostatic stress gradients under mechanical loading even without notch or crack [28,29]. In the present work, the hydrogen diffusion at the grain boundary was investigated by a proposed hydrogen diffusion model, which is based on the elastic response of the anisotropic behavior of crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the method with FIB enables researches to investigate the IGSCC in single GBs [24][25][26][27], it is difficult to manufacture specific single grain boundaries with respect to the irregularity of GBs and accurately measure the stress and strain distribution nearby GBs. us, the elastic response of anisotropic behaviors of the austenitic stainless steel crystal was presented by a constitutive model, and the effects of crystal orientation on the stress state near the GB were studied by the finite element method [28]. In this paper, a three-dimensional anisotropic finite element analysis, which focuses on the bicrystal with a symmetric tilt GB, is performed to obtain how crystal orientation and grain boundary inclination affect the stress state nearby the GB of the bicrystal.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the particularity of the welding process, the mechanical properties of the welded joints are not uniform and the metallographic changes of the materials, the discontinuity of the structure, the variation of the mechanical field, and the evaluation of the service life as well as the safety of the structure have always been the focus of scholars and engineers. Yang et al [7,8] investigated the effect of the elastic response of austenitic behavior of austenitic stainless steel, the orientation of crystal orientation, and the grain boundary (GB) dip angle under constant displacement by means of numerical simulation. e results showed that the larger the difference in the orientation of the twin crystal, the greater the strain inconsistency of the twin crystal.…”
Section: Introductionmentioning
confidence: 99%